The journey of Theophanes : travel, business, and daily life in the Roman east - Matthews, John (John Frederick) (Yale University Press, 2006)
In the early fourth century, a lawyer and public figure from the Nile valley city of Hermopolis made a six-month business related journey to Antioch. The day to day details are preserved on papyrus documents and offer a remarkable record of this journey, covering everything from distances traveled to daily food purchases, from medicinal supplies to fees paid for services. In this book, the classicist and historian John Matthews translates these important documents and places them in the wider context of the social history of the Graeco-Roman world. The memoranda relating to Theophanes' journey are presented within a historical narrative that offers an array of revelations on diet, travel, social relations, and other fascinating topics. This book creates an unprecedented account of daily life in the years preceding Emperor Constantine's rise to power in the eastern provinces of the Roman empire.